Fathers, Sons, and Hippies: Changes in American Blues in the 1960s and its Connection to the Counterculture - Gingerich, Joel (University of Waterloo, 2023)
This thesis examines the changing landscape of American blues music in the 1960s as well as the blues’ connection to the 1960s counterculture. This paper makes frequent use of oral histories from musicians and counterculture members. It also uses underground press publications to gauge the perceptions and opinions of the counterculture with respect to blues music. This project traces the journey of mid-century blues players from the Deep South up to northern industrial cities while arguing that commercialism and professionalism was a major part of their careers. This project then explores the younger generation of blues musicians (those born in the 1930s and early-1940s) as they developed relationships with the older generation of mid-century blues players. The younger generation, using a wide variety of influences, developed a new, energized subgenre of the blues during the 1960s. Older blues musicians in Chicago generously shared their music with younger musicians, both Black and White, while forming close, familial relationships with each other and sustaining the genre through the 1960s. Largely through the efforts of several notable blues artists, the genre became popular in White American circles. The mixed-race Paul Butterfield Blues Band largely increased the blues’ popularity with White people and the counterculture. While early-1960s White blues fans were largely members of the folk revival, valuing only acoustic Black country blues, the counterculture largely embraced the blues in all its forms by the late-1960s. Unlike the folk revivalists, the counterculture did not demand Black blues artists play folk-blues, and instead valued electric blues, albeit some problematic perceptions remained throughout the 1960s. The counterculture embraced blues music for many reasons. The genre was a basis for other popular genres like rock, it could be adapted and appropriated to fit countercultural views, and it was a method of rejecting the mainstream. The counterculture also developed a progressive blues cultural, using the blues to demonstrate solidarity with Black civil rights advocates. Blues musicians from Chicago found unprecedented popularity within the counterculture and greatly influenced countercultural musicians. Blues musicians likewise embraced the counterculture, adopting subversive lifestyles and incorporating countercultural motifs in their music by the mid-1960s. The paper concludes with a discussion of post-1960s blues, arguing against the myth that the blues stagnated and vanished since the end of the 1960s.
Keywords: blues; blues music; Muddy Waters; Michael Bloomfield; Mike Bloomfield; Paul Butterfield; Buddy Guy; counterculture; Nick Gravenites; Charlie Musselwhite; mentorship; Janis Joplin; Jimi Hendrix; Sam Lay; Big Joe Williams; Howlin' Wolf; B.B. King; appropriation; cultural appropriation; Ann Arbor; Ann Arbor Blues Festival; Taj Mahal; Paul Butterfield Blues Band; Chicago; San Francisco; Chicago blues; underground press; authenticity; commercialism; anti-commercialism